Cortical, Corticospinal, and Reticulospinal Contributions to Strength Training - Glover, Isabel S. (J Neurosci, 2020)
Following a program of resistance training, there are neural and muscular contributions to the gain in strength. Here, we measured changes in important central motor pathways during strength training in 2 female macaque monkeys. Animals were trained to pull a handle with one arm; weights could be added to increase load. On each day, motor-evoked potentials in upper limb muscles were first measured after stimulation of the primary motor cortex (M1), corticospinal tract (CST), and reticulospinal tract (RST). Monkeys then completed 50 trials with weights progressively increased over 8-9 weeks (final weight ∼6 kg, close to the animal's body weight). Muscle responses to M1 and RST stimulation increased during strength training; there were no increases in CST responses. Changes persisted during a 2 week washout period without weights. After a further 3 months of strength training, an experiment under anesthesia mapped potential responses to CST and RST stimulation in the cervical enlargement of the spinal cord. We distinguished the early axonal volley and later spinal synaptic field potentials, and used the slope of the relationship between these at different stimulus intensities as a measure of spinal input-output gain. Spinal gain was increased on the trained compared with the untrained side of the cord within the intermediate zone and motor nuclei for RST, but not CST, stimulation. We conclude that neural adaptations to strength training involve adaptations in the RST, as well as intracortical circuits within M1. By contrast, there appears to be little contribution from the CST. SIGNIFICANCE STATEMENT We provide the first report of a strength training intervention in nonhuman primates. Our results indicate that strength training is associated with neural adaptations in intracortical and reticulospinal circuits, whereas corticospinal and motoneuronal adaptations are not dominant factors.